2016
DOI: 10.1016/j.jds.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2, -9, and tissue inhibitor of MMP-2 gene polymorphisms in Taiwanese periodontitis patients

Abstract: Background/purpose Matrix metalloproteinases (MMPs) and tissue inhibitor of MMPs (TIMPs) have been shown to play an important role in the pathogenesis of tissue destruction in periodontitis. The associations between single nucleotide polymorphisms (SNPs) in the promoter regions of MMP-2, MMP-9, and TIMP-2 genes and the risk of aggressive periodontitis (AgP) and chronic periodontitis (CP) were investigated in a Taiwanese population. Materials and methods MMP-2 C-1306T, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
4
1
2
Order By: Relevance
“…Similar reports were observed by quite a few authors who have performed studies in Asian and Mixed populations like de Souza et al in Brazilian (mixed) population, Loo et al in Chinese (Asian) population, and several others. [ 13 35 40 41 42 43 44 45 ] On the other hand, the studies conducted in Caucasians have reported an association between MMP-9 SNP and CP; for instance, a study by Keles et al has found the association in Turkish (Caucasian) population which is in contrast with the current observation. [ 46 ] Meta-analyses by Pan et al and Mashhadiabbas et al have also found a moderate association in Caucasian population but nothing significant in Asian/mixed population.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar reports were observed by quite a few authors who have performed studies in Asian and Mixed populations like de Souza et al in Brazilian (mixed) population, Loo et al in Chinese (Asian) population, and several others. [ 13 35 40 41 42 43 44 45 ] On the other hand, the studies conducted in Caucasians have reported an association between MMP-9 SNP and CP; for instance, a study by Keles et al has found the association in Turkish (Caucasian) population which is in contrast with the current observation. [ 46 ] Meta-analyses by Pan et al and Mashhadiabbas et al have also found a moderate association in Caucasian population but nothing significant in Asian/mixed population.…”
Section: Discussioncontrasting
confidence: 89%
“…Of these case-control studies, for the MMP-9 -1562C>T polymorphism, 13 case-control studies in ten publications (1828) were available, including 1396 cases and 1709 controls. For the MMP-2 -753C>T polymorphism, six case-control studies (19,2123,27) involved a total of 693 cases and 636 controls. Among the 13 eligible studies for MMP-9 -1562C>T (rs3918242), four case-control studies (19,20,22,23) including 438 cases and 469 controls were undertaken in Caucasians (Czech and Turkey), seven case-control studies (21,24,2628) containing 827 cases and 1144 controls were conducted in Asians (China, Taiwan, and India), and two case-control studies (18,25) with 131 cases and 92 controls was performed in Latinos populations (Brazil and Colombia).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 13 eligible studies for MMP-9 -1562C>T (rs3918242), four case-control studies (19,20,22,23) including 438 cases and 469 controls were undertaken in Caucasians (Czech and Turkey), seven case-control studies (21,24,2628) containing 827 cases and 1144 controls were conducted in Asians (China, Taiwan, and India), and two case-control studies (18,25) with 131 cases and 92 controls was performed in Latinos populations (Brazil and Colombia). Of six case-control studies for MMP-2-753C>T (rs2285053), three case-control studies (19,22,23) including 328 cases and 391 controls were undertaken in Caucasians (Czech and Turkey) and three case-control studies (21,27) with 365 cases and 245 controls were performed in Asian (China and Taiwan) populations. The control populations of four studies deviated from Hardy–Weinberg equilibrium (HWE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially gelatinases, including the MMP-2 and MMP-9 enzymes, play a crucial role in hemostasis and the inflammatory response. Gene polymorphisms of metalloproteinases and their expression changes are observed in both PD and RA [ 42 , 43 ].…”
Section: Common Pathophysiological Pathways For Periodontitis and Rhementioning
confidence: 99%